Personal finance planning the determinants of demand on insurance policy / Mohd Azmi Mohd Ali - Mohd Ali, Mohd Azmi (Faculty of Business and Management, 2010)
Insurance is become an important issue nowadays to discuss. It is because many of Malaysian workers don’t notice about the important of the Insurance towards their self. At the end when something happen such as emergency cases that need immediate cash such as accident, they don’t have such a cash to finance their need. The past researcher shows that there are many factors that influence employee’s job satisfaction. Present research study revealed that there are five factors that could be the determinants of demand on insurance policy which are level of income, return, financial management knowledge, peoples consciousness and return. This study will be conducted in researcher resident at Taman Sri Raya, Ampang, Celcom (M) Sdn Bhd and Scope International (M) Sdn Bhd and involved total of 50 respondents.